The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1051/0004-6361/200811409
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of the flux cross-calibration of the XMM-Newton EPIC cameras

Abstract: Context. The second XMM-Newton serendipitous source catalogue, 2XMM, provides the ideal data base for performing a statistical evaluation of the flux cross-calibration of the XMM-Newton European Photon Imaging Cameras (EPIC). Aims. We aim to evaluate the status of the relative flux calibration of the EPIC cameras on board the XMM-Newton observatory (MOS1, MOS2, and pn) and investigate the dependence of the calibration on energy (from 0.2 to 12.0 keV), position of the sources in the field of view of the X-ray d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 12 publications
7
42
0
Order By: Relevance
“…While other missions report time variable low energy contamination, we do not think that such a problem exists for the Swift-XRT, because observations of low column density sources show no significant increases in the inferred column density with time. Of interest for our study, Mateos et al (2009) found that on-axis sources returned a MOS1/MOS2 flux that was 5−7% higher than the EPIC-pn flux in the 0.5−1.0 keV band. Stuhlinger et al (2010) conducted a similar analysis after processing the data with SAS v10.0 and compared the EPIC-MOS and EPIC-pn fluxes in several narrow bands using 2XMM sources that were not piled-up.…”
Section: Swift Xrtmentioning
confidence: 89%
“…While other missions report time variable low energy contamination, we do not think that such a problem exists for the Swift-XRT, because observations of low column density sources show no significant increases in the inferred column density with time. Of interest for our study, Mateos et al (2009) found that on-axis sources returned a MOS1/MOS2 flux that was 5−7% higher than the EPIC-pn flux in the 0.5−1.0 keV band. Stuhlinger et al (2010) conducted a similar analysis after processing the data with SAS v10.0 and compared the EPIC-MOS and EPIC-pn fluxes in several narrow bands using 2XMM sources that were not piled-up.…”
Section: Swift Xrtmentioning
confidence: 89%
“…For the 3XMM catalogues a simple approach has been adopted. ECFs were computed following the prescription of Mateos et al (2009), for energy bands 1 to 5 (0.2-0.5 keV, 0.5-1.0 keV, 1.0-2.0 keV, 2.0-4.5 keV and 4.5-12.0 keV respectively) and band 9 (0.5-4.5 keV), for full-frame mode, for each EPIC camera, for each of the Thin, Medium and Thick filters. A power-law spectral model with a photon index, Γ = 1.7 and a cold absorbing column density of N H = 3 × 10 20 cm −2 was assumed.…”
Section: Energy Conversion Factors (Ecfs)mentioning
confidence: 99%
“…In the soft energy regime below 0.9 keV, where the calibration is known to be least precise (Stuhlinger et al 2008;Mateos et al 2009), we use the isolated neutron star RX J1856.4−3754 to calibrate the EPIC spectra. RX J1856.4−3754 was established as a low-energy calibration target for missions such as Chandra, Suzaku, Swift, and XMM-Newton 1 , and exhibits a high soft X-ray and low optical flux.…”
Section: Introductionmentioning
confidence: 99%